2011
DOI: 10.1007/s10681-011-0446-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening and QTL analysis for drought tolerance in diploid potato

Abstract: Drought stress is a major abiotic constraint limiting crop production worldwide. Screening for drought tolerance and the traits that enhance drought tolerance is not straightforward in large mapping populations. In this study, we investigated the possibility of screening a mapping population in vitro for PEG-induced water deficit stress and recovery potential. We have measured several shoot and root growth parameters or traits in the C 9 E diploid potato mapping population. Significant variation was observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 47 publications
3
40
3
Order By: Relevance
“…These potato cultivars differ in their bulking time, growth rate and sensitivity to pathogens and various abiotic stresses. Many classical and molecular studies have been performed to identify the genetic loci responsible for agricultural traits using diploid potato plants (Anithakumari et al ., , ; Gebhardt, ; Khan et al ., ; Mani and Hannachi, ). Recently, due to the development of high‐throughput RNA sequencing techniques, which enable qualitative and quantitative global analyses of gene expression, novel approaches have been proposed to understand many physiological and agronomical traits in crop plants (Chen et al ., ; Gramazio et al ., ; Prince et al., ; Shankar et al ., ; Wang et al ., ; Zhang et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…These potato cultivars differ in their bulking time, growth rate and sensitivity to pathogens and various abiotic stresses. Many classical and molecular studies have been performed to identify the genetic loci responsible for agricultural traits using diploid potato plants (Anithakumari et al ., , ; Gebhardt, ; Khan et al ., ; Mani and Hannachi, ). Recently, due to the development of high‐throughput RNA sequencing techniques, which enable qualitative and quantitative global analyses of gene expression, novel approaches have been proposed to understand many physiological and agronomical traits in crop plants (Chen et al ., ; Gramazio et al ., ; Prince et al., ; Shankar et al ., ; Wang et al ., ; Zhang et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…) and potato (Anithakumari et al . ), and for leaf and silk growths in mapping population of maize (Welcker et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional QTLs for DTM and PH under both N conditions, Vmax, AUC and TYPP under high N conditions, and UCC under low N condition (in total about 11 QTLs) were co-located between 38-56cM on linkage group V. Previously QTLs associated with foliage traits were also identified in this region: QTLs for fresh biomass (Anithakumari et al, 2011), plant height, shoot fresh weight and shoot dry weight under drought stress and recovery condition (Anithakumari et al, 2012), for fresh and dry harvest index and stem diameter under drought and well-watered conditions (Khan et al, 2014) were identified in this region. Most of the QTLs detected in this region are more than 20cM downstream of the CDF1 gene, and may constitute different loci, independent of the earliness locus.…”
Section: Qtl Identificationmentioning
confidence: 89%
“…QTL analysis with a wide range of molecular markers provides opportunities not only for the identification of QTLs that determine the phenotypic value of a particular trait, but also for the analysis of the relationships between traits (Lebreton et al, 1995;Simko et al, 1997). In the last two decades many QTL analysis studies have been published on different traits of potato, such as flower color, foliage maturity, tuber skin texture, dry matter content, specific gravity and yield (McCord et al,2011), yield, agronomic and quality traits (Bradshaw et al,2008), tuber yield and starch content (Schafer-Pregl et al,1998, Werij et al, 2012, tuber dormancy (van den , tuber shape (Van Eck et al, 1994b), tuber skin color (Gebhardt et al,1989), tuber flesh color (Bonierbale et al, 1988), shoot fresh weight, tuber number, tuber weight and root length under drought stress and recovery conditions (Anithakumari et al, 2011;2012) and NUE related canopy cover traits under contrasting N regimes (Ospina, 2016). However, knowledge about the genetic dissection of NUE in potato is still limited and hardly any QTL has been published for NUE and NUE related traits of potato.…”
Section: Qtl Mappingmentioning
confidence: 99%
See 1 more Smart Citation